Diversification across the mountains: molecular Phylogenetics and phylogeography of the Chlorospingus ophthalmicus complex (aves, emberizidae) (2010)
Widely distributed Neotropical montane bird species are ideal study systems to understand the patterns and mechanisms of population differentiation and speciation. However, most phylogeographic studies have lacked samples from the northern Andes, a region recognized for its high species diversity and inter-population geographic variation. Here, we present one of the most comprehensive analysis of population differentiation on a widely distributed group of birds conducted so far, focusing on the Chlorospingus ophthalmicus complex (Aves, Emberizidae). By including a more complete taxonomic and geographic sampling in the northern Andes and Coastal Range of Venezuela than previous studies on the group, we found a high level of paraphyly within the complex, and suggest a more recent diversification in the group. Chlorospingus ophthalmicus is paraphyletic with respect to C tacarcunae, C. inornatus and C seniifuscus. Population genetic patterns suggest a northern origin of the group, possibly centered in the Madrean highlands of Mesoamerica. Colonization of South America possibly occurred after the final closure of the Isthmus of Panama. South American populations are separated into two highly divergent groups both genetically and morphologically distinct. Both groups possibly originated in the Central Andes and spread to northem latitudes, although at least one of them could have also colonized the Andes from the Chiriqui highlands. Climatic fluctuations during the Middle to Late Pliocene and the Pleistocene played an important role in the genetic and phenotypic differentiation of South American lineages. Populations isolated by Iowands showed higher levels of genetic differentiation compared to those separated by arid-river valleys or montane barriers. However, analyses detected some cases ofrecent gene flow across these barriers. Phenotypic evolution has been more conservative in Mexican and Central America than in South American lineages, and plumage characters used in traditional taxonomy exhibit high levels of homoplasy. Our results demostrate that phylogenetic, phylogeographic and biogeographic reconstructions are sensitive to the extent of taxonomic and geographic sampling in species groups of recent origin.